HOW WILL ARTIFICIAL INTELLIGENCE AFFECT THE LABOR MARKET? - Djabbarova Nilufar Furkatovna (European Science Publishing, 2024)
Purpose: Identify problems associated with the introduction of artificial intelligence technologies into the economic sphere and their impact on the labor market. Design/methodology/approach: The article analyzes the emerging barriers to the development of digitalization and artificial intelligence both in the labor market and in the economy. When conducting the research, general scientific and problem-oriented research methods were used, including observation and generalization. Findings: As a result of the analysis, it was revealed that the introduction of artificial intelligence into production and technological processes at the initial stage will have a negative impact on the labor market and on the situation in the economy and society. Originality/value: Directions for action to minimize the negative consequences of the spread of artificial intelligence and robotics in the economy are proposed.
Keywords: Artificial intelligence • Economic growth • Smart economy • digitalization • labor market • robotization of labor • new technologies.